ALEKSANDR FAYNBERG’S POEM “KUZ RUBOBI”: A PHILOSOPHICAL, AESTHETIC, AND CULTURAL MEANING (Ustozlar uchun, 2026)
This study provides a comprehensive line-by-line scholarly analysis of the poem “Kuz Rubobi”, a distinguished example of contemporary Uzbek poetry. Each line is examined for its thematic content, imagery, metaphors, symbolism, rhythm, musicality, and aesthetic and philosophical significance. By integrating natural imagery, love motifs, and musical elements, the poem constructs a reflective exploration of human existence, impermanence, and cosmic harmony. This analysis emphasizes the continuous interconnection of nature, emotion, art, and cultural motifs, demonstrating the poem’s enduring literary value.